Model of trust-based cooperative relationships in a supply chain - Ryciuk, Urszula; Nazarko, Joanicjusz (Journal of Business Economics and Management, 2020)
The study aimed to find factors affecting the development of trust-based cooperative relationships and test the links between them. For this study, the research framework was based on the notion that a cooperative relationship in a supply chain required commitment, cooperation and trust among the supply chain partners, with trust as a critical element. The other assumption was that the selection of partners with specific qualities was conducive to building cooperative relationships. The research was conducted on a sample of 226 companies using the CATI technique. In the study structural equation modelling was used. The obtained results confirmed the positive impact of partner qualities on trust and adaptation, of adaptation on commitment, of trust on cooperation and commitment, and of commitment on cooperation. New measurement scales were used that expanded the range of factors that affect the successful building of trust-based cooperative relationships in a supply chain.